Identidade(s) do sujeito masculino no programa humorístico sexo frágil - Bazza, Adélli Bortolon (2009)
Some themes have been appealing in the current discussions, among them it can stand out the insistence of the media in the appearance of the call "new man", thick way, a turned off subject of the sexist traditional patterns and identified to the speech of the equality. The speech on this new man happens directly about aspects of the identity of the masculine promoting yours (des)construction. This subject has been approached in several texts, among them in the program Fragile Sex. This one has as theme the subject of the relationships between the gender and it discusses that in the way of the humour, ridiculing the masculine. Due to the peculiarities of that program, it was taken as analysis aim the discursive production of the identity of the masculine materialized himself. It was intended, therefore, to analyze which identities of masculine are built in that speech. This analysis happens starting from a discursive perspective, allying knowledge of theoretical fields as Humour, Gender and Analysis of the Speech. Of the theory about humour concepts are mobilized as: laughter, parody and ridicule; of the studies on Gender: identity, manliness; and of the concepts of the Analysis of the Speech: identity, discursive formation (DF), heterogeneity, controversial interincomprehension, among others. In spite of the speech about the identities of masculine to constitute in all of the scenes of the program, the most representative scenes of the relationships of the masculine were cut out get even and with the feminine as corpus to be analyzed. In the analysis of the scenes, they were defined macho FD and equalitarian FD as those that argue inside of the discursive space of the relationships among the goods. Inside of that space, and in the confrontation of the own speeches those FDs, was looked for to show in that position was the masculine subject in the program. The systemization of the scenes showed that those subjects identify to the own speech of macho FD, conceiving a priority of the masculine in several fields, but they are forced to work with his other speech, that it is it of the equality. Those subjects create of him an imitation, because, due to the semantic restrictions of FD the one that is submitted, they translate the equality as a feminine superiority. The narrative sequence creates situations in that the macho speech, assumed as even by those subjects is shown inadequate. The speech of the program produces humour for approaching stereotypes, for presenting the subjects assuming macho positioning (usually criticized in the current society) and for representing a subject still lost, in search of identity.